1993
DOI: 10.1021/jm00073a012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure-activity relationships of a series of penicillin-derived HIV proteinase inhibitors containing a stereochemically unique peptide isostere

Abstract: A series of HIV-1 proteinase inhibitors was synthesized based upon a single penicillin derived thiazolidine moiety. Reaction of the C-4 carboxyl group with (R)-phenylalaninol gave amide 10 which was a moderately potent inhibitor of HIV-1 proteinase (IC50 = 0.15 microM). Further modifications based on molecular modeling studies led to compound 48 which contained a stereochemically unique statine-based isostere. This was a potent competitive inhibitor (Ki = 0.25 nM) with antiviral activity against HIV-1 in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…As proof of principle, L ‐alanine (Ala) and L ‐phenylalanine (Phe) were incorporated to demonstrate the preparation of olefin oligomers with a controlled sequence of side chains. Synthesis proceeded by coupling an Fmoc amino acid to N ‐Boc‐ p ‐phenylenediamine ( 1 , 5 ),13 followed by Fmoc deprotection ( 2 , 6 ) 14. The masked aldehyde moiety (Scheme ) was introduced by reacting the amine with diacetyl‐ L ‐tartaric anhydride, followed by basic removal of the acetyl protecting groups ( 3 , 7 ) 15.…”
Section: Methodsmentioning
confidence: 99%
“…As proof of principle, L ‐alanine (Ala) and L ‐phenylalanine (Phe) were incorporated to demonstrate the preparation of olefin oligomers with a controlled sequence of side chains. Synthesis proceeded by coupling an Fmoc amino acid to N ‐Boc‐ p ‐phenylenediamine ( 1 , 5 ),13 followed by Fmoc deprotection ( 2 , 6 ) 14. The masked aldehyde moiety (Scheme ) was introduced by reacting the amine with diacetyl‐ L ‐tartaric anhydride, followed by basic removal of the acetyl protecting groups ( 3 , 7 ) 15.…”
Section: Methodsmentioning
confidence: 99%
“…The residual dark brown foam was purified by chromatography on silica gel. Elution with a gradient of ethyl acetate/methanol from 9:1 to 4:1 gave the crude intermediate amide as a brown foam: 244 mg (37%); >H NMR (DMSO-d6) 1.27 (s, 9H), 1.42 (s, 3H), 1.61 (s, 3H), 2.25-2.42 (m, 2H), 2.8-3.1 (m, 4H), 3.5 (s, 1H), 3.55 and 3.56 (2s, 1H), 3.65 (m, 1H), 3.9 (m, 2H), 4.20 (m, 1H), 5.4-5.51 (m, 2H), 7.15-7.36 (m, 5H), 7.41 and 7.46 (2s 1H), 8.25 (m, 1H), 8.9 (m, 1H).…”
Section: C22h44n304bmentioning
confidence: 99%
“…With the aid of computer-assisted molecular modeling we then developed a series of potent inhibitors, e.g, 4 (IC50 = 4.6 nM), having significantly reduced molecular weight and containing a stereochemically unique statine dipeptide isostere. 8 In view of the success of this strategy based upon inhibitors containing a single penicillin-derived thiazolidine unit, we sought alternative means of interacting with the Si' and S2' subsites. The recently published work from Martin and co-workers9 on the biological properties of Ro 31-8959 (5) indicated that the decahydroisoquinoline moiety could fulfill this role and may well significantly affect the antiviral and pharmacokinetic properties of any "hybrid" molecules.…”
Section: Introductionmentioning
confidence: 99%
“…As proof of principle, l-alanine (Ala) and l-phenylalanine (Phe) were incorporated to demonstrate the preparation of olefin oligomers with a controlled sequence of side chains. Synthesis proceeded by coupling an Fmoc amino acid to N-Boc-p-phenylenediamine (1, 5), [13] followed by Fmoc deprotection (2,6). [14] The masked aldehyde moiety (Scheme 2 e) was introduced by reacting the amine with diacetyl-ltartaric anhydride, followed by basic removal of the acetyl protecting groups (3,7).…”
mentioning
confidence: 99%